2009
DOI: 10.1007/s10290-009-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

Real exchange-rate uncertainty and US foreign direct investment: an empirical analysis

Abstract: This paper empirically analyzes the impact of exchange-rate uncertainty, exchange-rate movements, and expectations on foreign direct investment (FDI). Using data on US outward FDI for the period 1984-2004 we examine two competing measures of exchange-rate volatility. While the standard measure yields a discouraging effect on FDI outflows in all industries the alternative risk specification reveals a clear distinction between manufacturing and non-manufacturing industries, with the latter showing a positive cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…9 According to Deichmann (2004), local market-oriented FDI generally prefers host countries with strong currencies. 10 Examples include: Görg and Wakelin (2002); Egger et al (2005); and Schmidt and Broll (2009). 11 Tallman (1988) finds that firms operating in a high-risk environment at home tend to invest more abroad.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…9 According to Deichmann (2004), local market-oriented FDI generally prefers host countries with strong currencies. 10 Examples include: Görg and Wakelin (2002); Egger et al (2005); and Schmidt and Broll (2009). 11 Tallman (1988) finds that firms operating in a high-risk environment at home tend to invest more abroad.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…Udomkerdmongkol, Morrissey, and Görg (2009) investigated the effect of exchange rates on US FDI flows to 16 emerging market countries and found that a cheaper currency attracts FDI. Schmidt and Broll (2009) empirically analyzed the impact of exchange rate on US FDI and found that a real appreciation of host country currency (that is a real depreciation of investment country currency) was associated with higher FDI flows. Lee (2015) examined the short-and long-run dynamic relationships between exchange rate level and FDI in Korea and found that a change in exchange rates negatively affects FDI flows in the long run, while in the short run, there is reciprocal feedback between the two variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Udomkerdmongkol et al (2009) found that expected devaluation implies that FDI of US is postponed in emerging countries. Schmidt and Broll (2009) empirically analyzed the impact of exchange rate on US FDI and found that expectations about an appreciation show a negative result.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The volatility of prices and foreign exchange rates may affect employment and the wage process in two ways, first through international trade in goods and services and second through foreign direct investment. 1 The intensified 1 See for example, Krugman (1989), Franke (1991), Schmidt and Broll (2009).…”
Section: Introductionmentioning
confidence: 98%